Cover Feature: Relevance of π‐Backbonding for the Reactivity of Electrophilic Anions [B12X11]− (X=F, Cl, Br, I, CN) (Chem. Eur. J. 40/2021). Issue 40 (24th June 2021) - Mayer, Martin; Rohdenburg, Markus; Kawa, Sebastian; Horn, Francine; Knorke, Harald; Jenne, Carsten; Tonner, Ralf; Asmis, Knut R.; Warneke, Jonas
Abstract : The vibrational frequency of CO, which binds to different electrophilic anions [B12 X11 ] ‐ (X=F, Cl, Br, I), is determined by an interplay of blue‐shifting electrostatics (blue beam between boron and carbon) and red shifting π‐backdonation (flames). For X=Cl, Br, I, (upper half) electrostatics dominates, while for X=F (bottom) π‐backdonation dominates and binds CO exceptionally strongly. Measured spectra are shown on the right. The band of unbound CO would be found at the position of the laser beam. More information can be found in the Full Paper by M. Mayer, J. Warneke, et al. (DOI: 10.1002/chem.202100949 ).